Leadership Style and Work Engagement: A Comparison of Private and Public Sector Firms in India - Mathew, Jain; Nair, Sridevi; Rajam, Kohila (Vision, 2024)
Post-privatization, public sector organizations were encouraged to borrow and learn from private sector firms. The popular belief was that the human resource practices followed by private sector organizations were far superior and more effective than those of the public sector organizations. However, this claim lacks empirical proof. This study adds to this body of knowledge by comparing the level of work engagement in private and public sector firms of India. Given that the leadership is crucial in setting the tone of an organization, the study also analyses the dominant leadership styles and their relationship to the levels of work engagement. The study is descriptive in nature and utilizes a structured questionnaire to collect data. Individuals currently employed in Indian public and private sector firms, in managerial roles, were invited to record their responses. The final sample consisted of 240 employees, with equal representation from both sectors. The collected data was then analysed using SPSS. The findings suggested that the dominant leadership styles were not significantly different in public and private sector organizations. Private sector employees were found to be more engaged and the leadership style appeared to be significantly related to the levels of engagement in public sector firms only.
Keywords: Leadership Styles; Private Sector; Public Sector; Work Engagement; India